TANGGUNG JAWAB, KEADILAN DAN KEBENARAN AKUNTANSI SYARIAH (IAIN Tulungagung, 2017)
Accountancy can form and be formed by environment where about theaccountancy developed. Accountancy expanding in this time is nothing fromcapitalism ideology. Capitalism born from rational values, liberalism values,and materialism values with understanding assuming society prosperity willonly be obtainable production is well delivered to ever y individual giving infinitefacility for resources management in reaching target. While Islam as alternativeideology needed as comparator expected can fulfill accountancy society demandwhich own is responsibility, justice and justification value. Accountancy conceptconsist of financial statement target, postulate, theoretical concept, accountancytechnique and principle influenced by capitalist ideology with rational value,freedom, and assess items. Responsibility, Justice and justification expectedmay not be separated from having shariate accountancy based on tauwheedAkuntansi dapat membentuk dan dibentuk oleh lingkungan di mana akuntansi dikembangkan. Akuntansi berkembang saat ini adalah apa-apa dari ideologi kapitalisme. Kapitalisme lahir dari nilai-nilai rasional, nilainilai liberalisme, dan nilai-nilai materialisme dengan pemahaman asumsi kesejahteraan masyarakat hanya akan produksi diperoleh baik dikirim ke setiap pemberian fasilitas terbatas individu untuk pengelolaan sumberdaya dalam mencapai sasaran. Sementara Islam sebagai ideologi alternatif diperlukan sebagai pembanding diharapkan dapat memenuhi kebutuhanmasyarakat akuntansi yang memiliki tang gung jawab, keadilan dan justifikasinilai. Konsep Akuntansi terdiri dari sasaran keuangan pernyataan, postulat,konsep teoritis, teknik akuntansi dan prinsip dipengaruhi oleh ideologikapitalis dengan nilai rasional, kebebasan, dan menilai item. Tanggung Jawab,Keadilan dan justifikasi diharapkan tidak dapat dipisahkan dari memilikishariate akuntansi berdasarkan tawhid.